Risk factors for developing into critical COVID-19 patients in Wuhan, China: A multicenter, retrospective, cohort study. (August 2020) - Liu, Dan; Cui, Pengfei; Zeng, Shaoqing; Wang, Siyuan; Feng, Xinxia; Xu, Sen; Li, Ruyuan; Gao, Yue; Yu, Ruidi; Wang, Ya; Yuan, Yuan; Li, Huayi; et al.
Abstract: Background: The ferocious global assault of COVID-19 continues. Critically ill patients witnessed significantly higher mortality than severe and moderate ones. Herein, we aim to comprehensively delineate clinical features of COVID-19 and explore risk factors of developing critical disease. Methods: This is a Mini-national multicenter, retrospective, cohort study involving 2, 387 consecutive COVID-19 inpatients that underwent discharge or death between January 27 and March 21, 2020. After quality control, 2, 044 COVID-19 inpatients were enrolled. Electronic medical records were collected to identify the risk factors of developing critical COVID-19. Findings: The severity of COVID-19 climbed up straightly with age. Critical group was characterized by higher proportion of dyspnea, systemic organ damage, and long-lasting inflammatory storm. All-cause mortality of critical group was 8545%, by contrast with 058% for severe group and 018% for moderate group. Logistic regression revealed that sex was an effect modifier for hypertension and coronary heart disease (CHD), where hypertension and CHD were risk factors solely in males. Multivariable regression showed increasing odds of critical illness associated with hypertension, CHD, tumor, and age ≥ 60 years for male, and chronic obstructive pulmonary disease (COPD), chronic kidney disease (CKD), tumor, and age ≥ 60 years for female. Interpretation: We provide comprehensive front-line information about different severity of COVID-19 and insights into different risk factors associated with critical COVID-19 between sexes. These results highlight the significance of dividing risk factors between sexes in clinical and epidemiologic works of COVID-19, and perhaps other coronavirus appearing in future. Funding: National Science Foundation of China .